Development and evaluation of targeted marginal land mapping approach in SWAT model for simulating water quality impacts of selected second generation biofeedstock. (July 2016) - Singh, Gurdeep; Saraswat, Dharmendra
Abstract: Information about location of marginal lands in a watershed is of interest to those who view these areas as potential land for producing biofuel crops. However, representing marginal lands into a distributed model such as the Soil and Water Assessment Tool (SWAT) is a challenge due to a rigid framework used for watershed sub-division. In this study, we developed a Geographic Information System (GIS) based approach for implementing targeted land use i.e. marginal lands into the SWAT model and evaluated the applicability of the approach on a 8-digit Hydrologic Unit Code (HUC) watershed scale. Comparative results showed that conventional targeting approach overestimates the benefit of targeting marginal lands for Alamo switchgrass ( Panicum virgatum, L) and giant miscanthus (Miscanthus × giganteus) production due to simulation of larger area under marginal land category. Compared to baseline condition, which corresponds to no biofuel crop production on marginal lands, the pollutant losses under new targeting approach with simulation of Alamo switchgrass and giant miscanthus on marginal lands were substantially lower. The new targeting approach advances the science behind landscape representation in the SWAT model – that has potential to be used in future targeting studies. Highlights: New simulation approach locates marginal land with a correct spatial definition. Conventional targeting approaches could overestimate the benefits of targeting. The new approach advances the science behind landscape targeting. New simulation approach can prove useful in reporting the most accurate results.